2016
DOI: 10.3762/bjnano.7.12
|View full text |Cite
|
Sign up to set email alerts
|

Chemical bath deposition of textured and compact zinc oxide thin films on vinyl-terminated polystyrene brushes

Abstract: SummaryIn this study we investigated the influence of an organic polystyrene brush on the deposition of ZnO thin films under moderate conditions. On a non-modified SiOx surface, island growth is observed, whereas the polymer brush induces homogeneous film growth. A chemical modification of the polystyrene brushes during the mineralization process occurs, which enables stronger interaction between the then polar template and polar ZnO crystallites in solution. This may lead to oriented attachment of the crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…There are many examples of descriptions of this process indicating different reaction steps, which are based on the equilibrium between the precipitation and dissolution of zinc oxide/hydroxide [ 15 ]. It is complicated because every factor of procedure, such as the kind and amount of reagents [ 16 , 17 ], time [ 18 ], and the temperature [ 12 ] of the reaction, has a significant influence on the obtained particles. It could be concluded that a smaller concentration of zinc nitrate and HMT, resulted in less zinc oxide (hydroxide), with a smaller average number of particles, being deposited on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples of descriptions of this process indicating different reaction steps, which are based on the equilibrium between the precipitation and dissolution of zinc oxide/hydroxide [ 15 ]. It is complicated because every factor of procedure, such as the kind and amount of reagents [ 16 , 17 ], time [ 18 ], and the temperature [ 12 ] of the reaction, has a significant influence on the obtained particles. It could be concluded that a smaller concentration of zinc nitrate and HMT, resulted in less zinc oxide (hydroxide), with a smaller average number of particles, being deposited on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these varied applications, several methods including thin films and polymeric approaches have been employed to deposit ZnO. Some of the thin film methods used include; chemical vapour deposition [12,13,14], chemical bath deposition [15], laser deposition [16,17], spray pyrolysis [18], magnetic sputtering [19], thermal oxidation [20], molecular beam epitaxy [21] and electrospraying [8]. ZnO fibre on the other hand has been synthesized using template [22] and electrospinning [23,24] methods.…”
Section: Introductionmentioning
confidence: 99%
“…2 ). Investigation of the deposition of ZnO films on the bare substrate showed that without template only island growth occurs [ 25 ]. In comparison, the ZnO films on the highly negatively charged PEL ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, organic templates are used to modify the surface of the substrate. Especially self-assembled monolayers (SAMs) [ 23 24 ], thin polymer brushes [ 25 ] or polyelectrolyte multilayers (PEL) [ 26 ] were successfully applied for the deposition of ZnO thin films. With these molecules, a multitude of different functionalities are available, e.g., amino-, carboxylate or sulfonate groups for hydrophilic or alkyl groups and fluorine atoms for hydrophobic modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation